The Association of Electric Cigarette Using Period with Respiratory Symptoms in Male E-Cigarette User - Saragih, M. Khairul Aswin; Tarigan, Amira P. (CoinReads Media Prima, 2024)
Introduction: The increasing trend of e-cigarettes user is often found in productive young people, especially those who are undergoing education. The use of electric cigarettes can cause respiratory complaints such as coughing, coughing up phlegm and shortness of breath. To identify the subject characteristic and to examine association between e-cigarette using period with respiratory symptoms in e-cigarrette male user who are undergoing education in Senior High School and Medical Education in Medan Methods: This study took samples of research subjects using two groups, where each group numbered 15 people, these groups were entered according to the inclusion and exclusion criteria, with the pearson correlation test using the ATSQ instrument to assess respiratory symptoms. Results: The age range of 21-25 years is the most users of e-cigarettes (43.4%), the most education is in the form of professional general practitioner education in this study (43.3%). Respiratory complaints that were often felt by subjects were coughing in the morning which occurred most often 1-2 times a week and shortness of breath during exercise which appeared less than once per week. The pearson test shows r count > r table (0.883 > 0.641) and is positive. Conclusion: There is an association between e-cigarette using period with respiratory symptoms, where the longer you use, the more severe the respiratory symptoms will be.